Associations between neonatal distress and effortful control in preterm born toddlers: does parenting stress act as a moderator?. (July 2014) - Voigt, Babett; Brandl, Alexa; Pietz, Joachim; Pauen, Sabina; Kliegel, Matthias; Pöschl, Johannes; Reuner, Gitta
Abstract : Objectives: Self-regulation is a key factor in cognitive and behavioural development. The present work explored the link between neonatal distress and effortful control skills of preterm born toddlers as well as parenting stress as a moderator of this association. Methods: The sample comprised 119 preterm born children without major neurological complications (periventricular leucomalacie, Grade 3 or 4 intraventricular hemorrhage, seizures) or sensory impairment. Assessment involved effortful control (multitask behavioural battery, parent report; 24 months corrected age [CA]), parenting stress (parent-report; 12, 24 months CA), and the number of potentially distressful neonatal intensive care procedures as well as severity of illness during the neonatal period (retrospective chart review). Results: Exposure to a higher number of distressful procedures was related to lower effortful control (behavioural measures only) at the CA of 24 months when adjusting for gestational age, severity of illness and socioeconomic status. In contrast to hypotheses, lower parenting stress did not buffer distress-related effects on effortful control, but independently facilitated the emergence of higher effortful control skills. Conclusion: Findings highlight the role of early adversity for the emergence of self-regulatory difficulties and suggest multiple opportunities for interventions yielding on the promotion of self-regulation in preterm born children.